Evidence for massive emission of methane from a deep‐water gas field during the Pliocene - Foschi, M; Cartwright, JA; Macminn, CW; Etiope, G (National Academy of Sciences, 2020)
Geologic hydrocarbon seepage is a natural atmospheric source of methane, considered to prevail in terrestrial and shallow‐water areas; deep‐water methane seepage is expected to have no atmospheric impact, as gas is typically consumed throughout the water column. Here, we present evidence for a sudden expulsion of a reservoir‐sized quantity of methane from a deep‐water seep during the Pliocene, resulting from natural gas reservoir overpressure. Combining 3D seismic data, borehole data and fluid‐flow modelling, we estimate that 18–27 of the 23–31 Tg released at the seafloor could have reached the atmosphere over 39–241 days. This emission is ~10 % and ~28 % of present‐day, annual natural and petroleum‐industry methane emissions, respectively. While no such ultra‐seepage events have been documented in modern times and their frequency is unknown, seismic data suggest they were not rare in the past and potentially occur at present in critically pressurized reservoirs. This neglected phenomenon can influence decadal changes of atmospheric methane.